Climate change effects and adaptation strategies in the wine sector: A quantitative literature review - Sandro Sacchelli; Sara Fabbrizzi; Silvio Menghini (Wine Economics and Policy, 2016)
This paper presents a quantitative literature review focusing on how scientific research analysed climate change impact on wine chain as well as potential adaptation strategies. The work is based on content analysis and text mining and takes into account researches from 1990 to 2015. A particular emphasis was given to the evaluation of suggested or implemented adaptation strategies at both global and national levels. Data were analysed using cluster analysis, multidimensional scaling and specificity evaluation. Results show that the study of climate change impacts on the wine sector is a recently emerging research topic. Adaptation strategies have not yet been explored thoroughly in the literature, and in-depth uncertainty quantification is also needed. Finally, additional research gaps and potential future issues are suggested.
Keywords: 330; Climatic impact; Content analysis; Multiscale review